"17" is odd and "seventeen" is even: Meaning and physical form in stimulus-parity synaesthesia. Issue 9 (September 2018) - White, Rebekah C; Dumbalska, Tsvetomira; Duta, Mihaela D; Nation, Kate
For individuals with stimulus-parity synaesthesia, eliciting stimuli (e.g., shapes, numbers, letters, colours) trigger a compelling feeling of oddness or evenness. Given that (a) many inducers are conceptual and (b) parity is itself a conceptual property, one questions whether stimulus-parity synaesthesia will be a categorically higher subtype, such that the conceptual properties of stimuli will be crucial in determining parity. We explore this question as it applies to Synaesthete R, one of only two stimulus-parity synaesthetes known to the contemporary literature. In Experiments 1 and 2, we examine whether parity is tied to concepts or percepts, asking, for example, whether a rectangle is even regardless of whether it is presented as an image or a word. Our results indicate that the parity of shapes (words and images), numbers (words, digits, and Roman numerals), and letters (lowercase and uppercase) differs according to the stimulus format, supporting a perceptual explanation. In Experiment 3, we examine the parity of colour stimuli, showing a systematic relationship between the measurable physical properties of hue, saturation, and lightness and synaesthetic parity. Despite the conceptual nature of inducers and concurrents, for Synaesthete R, stimulus-parity synaesthesia is a lower subtype; perceptual properties of stimuli determine parity.